1956
DOI: 10.1175/1520-0477-37.4.160
|View full text |Cite
|
Sign up to set email alerts
|

A Spot Climate Recorder

Abstract: In agricultural research as well as in applied climatology as a whole, there is an increasing demand for portable meteorological field equipment capable of recording continuously more environmental factors than the conventional hygro-thermograph. The spot climate recorder described can register dry bulb, wet bulb, soil, and black globe temperatures, and wind direction and velocity on either daily or weekly charts, whichever is best for the climate survey. If desired, all these elements can be registered on one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1957
1957
1974
1974

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…1 and 2) measured temperature and relative humidity a t 1 m above ground level in a standard weather shelter, rainfall at ground level, and wind speed and direction by a spot climate recorder with detectors 2 m above ground level. This last instrument (28) (Fig. 2) was designed in the Department of Agricultural Engineering, University of California, Davis, and constructed by Symens Mfg.…”
Section: Methodsmentioning
confidence: 99%
“…1 and 2) measured temperature and relative humidity a t 1 m above ground level in a standard weather shelter, rainfall at ground level, and wind speed and direction by a spot climate recorder with detectors 2 m above ground level. This last instrument (28) (Fig. 2) was designed in the Department of Agricultural Engineering, University of California, Davis, and constructed by Symens Mfg.…”
Section: Methodsmentioning
confidence: 99%
“…Eight years of wind recordings were available at Davis from an 8-meter mast registering on a Bendix-Friez quadruple recorder. A three-year recording was available for Grimes, obtained from a portable spot-climate recorder [5] that uses an anemometer height of 2 meters. Direct comparison of wind velocity at these two stations is not attempted because of the different anemometer heights, station exposures (only Grimes was un-obstructed), and the different threshold velocities.…”
Section: Diurnal Periods Of Low Wind Velocitymentioning
confidence: 99%
“…Results indicated that the increase in tempera ture with increase in diameter was rapid up to 4 to 5 inches, and was low above a diameter of 6 inches. Schultz and Brooks (1956) stated that the lags of larger globes are not a serious problem, and even suggested increas ing the mass of the globes to reduce temperature unrest.…”
Section: Physical Environmentmentioning
confidence: 99%